Rancangan Sistem Informasi Bengkel ”Fast Auto” - Darudiato, Suparto (ComTech: Computer, Mathematics and Engineering Applications, 2010)
A car workshop requires an integrated information system to support business processes. The purpose of this study is to analyze the system information on the “Fast Auto” Car Workshop in order to identify the problem and to propose a new system. In analyzing and designing new systems, object-oriented methodology is applied through the collection of data based on direct observation in the field. Analysis results were used on designing the proposed information system that capable to support the operational activities of the workshop. As the result it will be a good information system and can be fully achieved the effectiveness and efficiency in the operational activities, therefore the executive can have the information that needed to make up a right decision.